On the scope and characteristics of relapse when treating severe destructive behavior. Issue 3 (15th March 2022) - Mitteer, Daniel R.; Greer, Brian D.; Randall, Kayla R.; Haney, Sarah D.
Abstract : Prior studies on treatment relapse have typically examined the prevalence of resurgence or renewal of target behavior (e.g., destructive behavior) in isolation. This study analyzed both types of relapse during 25 consecutive treatments involving functional communication training during worsening reinforcement conditions for alternative behavior (i.e., schedule thinning) or following context changes. We also examined disruption of alternative behavior (i.e., functional communication requests, compliance). Resurgence and renewal of destructive behavior occurred in 76% and 69% of treatments, respectively, and in approximately a third of changes in reinforcement or context. Relapse of destructive behavior predicted alternative‐response disruption and vice versa; the co‐occurrence of these two events always exceeded the background probabilities of either event occurring in isolation. General reductions in treatment efficacy occurred across changes in reinforcement or context, with no apparent decrease in likelihood in later transitions. We discuss implications of our findings with respect to future studies examining treatment durability.